Profiling Atlantic salmon B cell populations: CpG-mediated TLR-ligation enhances IgM secretion and modulates immune gene expression - Jenberie, Shiferaw; Thim, Hanna Leena; Sunyer, J Oriol; Skjødt, Karsten; Jensen, Ingvill; Jørgensen, Jorunn B (Scientific Reports, 2018)
Source at https://doi.org/10.1038/s41598-018-21895-9 . Licensed CC BY-NC-ND 4.0. While TLR-activated pathways are key regulators of B cell responses in mammals, their impact on teleost B cells are scarcely addressed. Here, the potential of Atlantic salmon B cells to respond to TLR ligands was shown by demonstrating a constitutive expression of nucleic-acid sensing TLRs in magnetic sorted IgM + cells. Of the two receptors recognizing CpG in teleosts, tlr9 was the dominating receptor with over ten-fold higher expression than tlr21 . Upon CpG-stimulation, IgM secretion increased for head kidney (HK) and splenic IgM + cells, while blood B cells were marginally affected. The results suggest that CpG directly affects salmon B cells to differentiate into antibody secreting cells (ASCs). IgM secretion was also detected in the non-treated controls, again with the highest levels in the HK derived population, signifying that persisting ASCs are present in this tissue. In all tissues, the IgM + cells expressed high MHCII levels, suggesting antigen-presenting functions. Upon CpG-treatment the co-stimulatory molecules cd83 and cd40 were upregulated, while cd86 was down-regulated under the same conditions. Finally, ifna1 was upregulated upon CpG-stimulation in all tissues, while a restricted upregulation was evident for ifnb , proposing that salmon IgM + B cells exhibit a type I IFN-response.